2002
DOI: 10.7227/rie.67.6
|View full text |Cite
|
Sign up to set email alerts
|

Citizenship Education in Chinese Schools

Abstract: E ducation for citizenship has become a key concern of educational policy and debate in economically advanced countries as well as in developing countries. The question of what constitutes education for citizenship in different nations is critical in both national and international contexts. China is no exception as it emerges from its most recent era of self-enforced isolation, and much can be drawn from China's transformation from the classical idea of its people being subjects of an absolute monarchy claimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In particular, it aims to foster obedience, socialism and communism among university students, but ignores the importance of personal development and civic rights. In other words, curriculum development in ideological and political education at university level has failed to keep pace with the demands of the times, due to its long-term neglect of research on theoretical issues and curriculum design (Chen and Reid, 2002). The participants in the interviews have expressed their definite dissatisfaction towards current ideological and political education, and the most striking argument proposed was that the university curriculum could not provide relevant civic opportunities according to students' ideal notions of civic participation.…”
Section: The Limited Effect Of the Citizenship Curriculum On Universimentioning
confidence: 99%
“…In particular, it aims to foster obedience, socialism and communism among university students, but ignores the importance of personal development and civic rights. In other words, curriculum development in ideological and political education at university level has failed to keep pace with the demands of the times, due to its long-term neglect of research on theoretical issues and curriculum design (Chen and Reid, 2002). The participants in the interviews have expressed their definite dissatisfaction towards current ideological and political education, and the most striking argument proposed was that the university curriculum could not provide relevant civic opportunities according to students' ideal notions of civic participation.…”
Section: The Limited Effect Of the Citizenship Curriculum On Universimentioning
confidence: 99%
“…Many studies (e.g., Chen & Reid, 2002;Lee, 1996;Lee & Ho, 2008) showed that, while still emphasizing patriotism, collectivism and the leadership of Communist Party of China (CPC), since the 1978 Open Door reforms China has gradually reduced CE's political/ideological content and broadened its focus to include children's personal growth; their family, community, national and global roles; family, social and vocational ethics; and global awareness. Law (2011) and Wang and Tan (2014) showed that Chinese CE's ideological dualism (capitalism versus communism) has been gradually replaced by a more accommodative multidimensional framework centered on students' community spheres (family, school, local, national and international).…”
Section: Approaches To Teaching/learning Cementioning
confidence: 99%
“…Although the revised moral education embodies an increased focus on the individual and is more reflective, one obstacle for reflective morality has been a lack of focus on contemporary topics, which may be a lasting effect from previous iterations marking a struggle for change (Chen & Reid, 2002). A challenge of reconceptualizing moral education in many post-communist countries is that the education teachers and parents received is quite different from new iterations (BukBerge, 2006).…”
Section: Reflective Thinking and Improving The Process Of Inquirymentioning
confidence: 99%